The Comparison of Duration Endotracheal Tube Insertion Using Aerosol Box And without Aerosol Box in Elective Surgery Patients in the Covid-19 Pandemic - Zulkifli; Agustina Br Haloho; Legiran; Muhammad Ikhsan Kartawinata (HM Publisher, 2021)
Introduction. The aerosol box can reduce the risk of droplet and aerosol transmission from the patient to the operator when performing intubation, but in practice, an aerosol box makes the glottis visualization less evident, and the operator moves less space with less space the aerosol box. This study aimed to compare ETT duration using an aerosol box and without an aerosol box using a video laryngoscope. Methods: This study was a clinical trial with a post-test-only control design. The study was carried out from February 2021 to May 2021 at the Central Operating Theater of dr. Mohammad Hoesin General Hospital Palembang. The sample in this study was all patients who underwent elective surgery under general anesthesia using intubation at the Central Surgical Installation of dr. Mohammad Hoesin Palembang. After the data is collected, it is analyzed using the SPSS 22.0 program with the appropriate test. Results. There were no differences in subject characteristics (age, sex, BMI, Mallampati score, TMD, Cormack Lehane, limited mouth opening, short neck, limited mouth movement) between the group using the aerosol box and the group without the aerosol box. The duration of intubation without an aerosol box is 30.67 + 2.63 seconds, and using an aerosol box is 44.53 + 2.89 seconds. There was a significant difference between the two groups in the duration of patient intubation (p < 0.001). However, there was no significant difference in complications in the two groups (p >0.05). Conclusion. The duration of the endotracheal tube insertion using an aerosol box is more extended than without an aerosol box in elective surgery patients.